Indigodole E from Strobilanthes cusia exhibits anti-IL-17A effect. Issue 23 (1st December 2022) - Lee, Chia-Lin; Wang, Chien-Ming; Yen, Hung-Rong; Song, Ying-Chyi; Chen, Chao-Jung
Abstract: One new indazole alkaloid, indigodole E (1 ), was isolated from a traditional Chinese medicine Qing Dai prepared from the aerial parts of Strobilanthes cusia . The structure of 1 was elucidated by NMR, MS, UV, and IR spectra as well as optical rotation. Additionally, compound 1 could obviously inhibit not only IL-17A protein production at concentrations from 1.25 to 2.5 μg/mL, but also IL-17 gene expression at concentrations from 5.0 to 10.0 μg/mL without cytotoxicity toward Th17 and Jukat cells, respectively. Overall, indazole analogue 1 could be the anti-IL 17 A contributor of Qing Dai in this investigation. Graphical Abstract: UF0001